On fuzzy number calculus - Kosiński, Witold (1946-2014) (Zielona Góra: Uniwersytet Zielonogórski)
Some generalizations of the concept of ordered fuzzy numbers (OFN) are defined to handle fuzzy inputs in a quantitativeway, exactly as real numbers are handled. Additional two structures, an algebraic one and a normed (topological) one, areintroduced to allow for counting with a more general type of membership relations.
Keywords: fuzzy numbers; bounded variation